STIGMA SOSIAL TERHADAP PEREMPUAN EKS NARAPIDANA DAN DAMPAKNYA PADA PELUANG KERJA - Subroto, Mitro; Rahman, Refi (Ensiklopedia of Journal, 2024)
Abstract: Social stigma against female ex-inmates significantly hampers their chances of gaining employment upon release from prison. Historically, women in the penal system face unique challenges compared to their male counterparts, including higher rates of caregiving responsibilities and lower pre-incarceration employment levels. The stigma associated with a criminal record leads to widespread discrimination, where employers frequently reject resumes containing past convictions without considering relevant skills and experiences. Additionally, the absence of laws regulating the disclosure of criminal records exacerbates the problem, further limiting job opportunities for ex-inmates. Research indicates that women with criminal records encounter substantial barriers when attempting to reintegrate into society, including mental, financial, and physical hurdles. Focus group discussions and interviews reveal that younger women struggle primarily with limited work experience and a criminal record, whereas older women confront compounded obstacles like aging, historical abuse, and extended incarceration periods. The study emphasizes the urgent need for legislative reforms and educational/training programs aimed at mitigating these effects and enhancing the employability of formerly incarcerated females. Keywords: stigma, female ex-inmates, employment opportunities, criminal records